(untitled) (Altre Modernità, 2010)
The interaction between communication, politics and passion holds reality together, the analysis of which leads to a better knowledge of the foundation of the civil bond. If the concepts individually offer a first approach to the comprehension of this interaction, their common use of language gives us a deeper understanding of the public word (concerning public questions and addressed to the people) as a medium towards a collective will and as an instrument to transform single attitudes. This aim is achieved through the clever expression of one’s own or other’s feelings or emotions as learnt through the rhetorical art: the ethos or pathos construction is thus a sign of how the passion underlying public communication has a political end. Nevertheless, the cognitional nature of passion lets us understand that this is the real condition of the civil bond and therefore the origin of both politics and communication.